STRATEGIC PARTNERSHIPS AND SOCIAL PROGRESS: THE ROLE OF JICA IN TRANSFORMING EDUCATIONAL INFRASTRUCTURE AND HUMAN DEVELOPMENT IN UTTARAKHAND - Kalra, Mohit; Nautiyal, Arpan; Singh, Krishnapal (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This research paper critically examines the pivotal role of the Japan International Cooperation Agency (JICA) in fostering educational infrastructure and human development within Uttarakhand, India. As a significant development partner, JICA has demonstrably contributed to fortifying institutional capacities, elevating vocational education standards, and championing equitable access to quality learning across the state. Through targeted interventions, notably the “Project for Strengthening of Human Development in Uttarakhand” (2017–2023), JICA has facilitated the modernization of key educational entities, including District Institutes of Education and Training (DIETs), the State Council of Educational Research and Training (SCERT), Industrial Training Institutes (ITIs), and polytechnics. This study examines how JICA's collaborative approach, which prioritizes institutional ownership, community involvement, and long-term sustainability, fits in with more general goals for human capital development. The study evaluates the project's results in important areas such gender inclusion in technical education, teacher training effectiveness, and youth employability using a mixed-methods methodology that draws on both primary and secondary data. The analysis notes noteworthy accomplishments but also points up implementation issues and areas that need improvement. The results highlight JICA's interventions in Uttarakhand as a powerful example of strategic international collaboration, successfully tying infrastructure development to human empowerment and making a significant contribution to the socioeconomic resilience and advancement of the region.